(untitled) (Clinics, 2021)
OBJECTIVES: The aim was to prospectively assess the variation in liver stiffness (LS) and the associated factors for LS progression in a cohort of naïve, non-responder (NR), and sustained virological response (SVR) chronic hepatitis C (CHC) patients. METHODS: This was a longitudinal study on CHC patients prospectively followed with serial elastography (Fibroscan®). The LS progression rate was determined, and the associated factors for progression were assessed using multiple linear regression analysis. RESULTS: A total of 406 patients were followed up for 44 (35-53) months [naïve (29%), NR (24%), and SVR (47%)]. At the end of the follow-up period, the SVR group had a significant decrease in LS [11.8 (9.2) vs. 8.8 (8.4) kPa (p<0.001)], the NR group had a significant increase in LS [6.6 (5.2) vs. 7.1 (4.5) kPa (p=0.069)], and the naïve group had no change in LS [6.3 (3.0) vs. 6.0 (3.8) kPa (p=0.22)]. The related factors for LS progression were lack of SVR (p=0.002) and diabetes (p=0.05). In the non-diabetic SVR group, a negative rate of progression (-0.047 kPa/month) was observed, whereas in the diabetic SVR group, a positive rate of progression (+0.037 kPa/month) was observed. The highest rate of progression was observed in NR with diabetes at the rate of +0.044 kPa/month. CONCLUSION: LS in diabetes patients progresses despite SVR, suggesting the need for a close follow-up of this group post-treatment considering the risk of progression of liver disease even after SVR.